Knowledge and attitude of Universiti Kebangsaan Malaysia (UKM) medical students on forest bathing - Aaron Ignatius; Teo, Sze Lynn; Wan Muhammad Aiman Hazimin; Fahninazirah Ahmad; Aeinaa Shida; Rafidah Hod; Hanizah Mohd Yusoff; Ahmad Fariz Mohamed; Rozita Hod (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Forest bathing or Shinrin-Yoku is a practice of being mindful of nature and it offers multiple health benefits in both physiological and psychological factors. This study aimed to determine the knowledge and attitude of Universiti Kebangsaan Malaysia (UKM) medical students towards forest bathing and its relationship with the sociodemographic factors. A total of 165 UKM medical students were recruited using proportionate stratified random sampling. The subjects were then categorized based on the academic year (Year 1 - Year 5) from May 2021 until September 2021. Exclusion criteria includes those who deferred their academic year and/or who were hospitalized. A questionnaire was given via a google form consisting of sociodemographic data details and 15 questions for each knowledge and attitude on forest bathing. The prevalence of good knowledge and good attitude of UKM medical students towards forest bathing were 64.2% (n=106) and 50.9% (n=84) respectively. Female medical students had a good knowledge (n=63, 73.3%) and good attitude (n=52, 60.5%) compared to male medical students’ knowledge (n=43, 54.4%) and attitude (n=32, 10.5%), with a p-value of 0.012 and 0.010 respectively. Otherwise, other sociodemographic factors including race, medical year and level of lifestyle did not affect participants’ knowledge and attitude on forest bathing. Majority of UKM medical students have a higher prevalence of good knowledge compared to good attitude on forest bathing. Therefore, we recommend forest bathing to be integrated into the medical curriculum as part of awareness especially in male medical students.